Shipowner’s Impact on Planned Maintenance System Database Quality Grades Resemblance Equalization - Stazić, Ladislav; Komar, Ivan; Mihanović, Luka; Mišura, Antonija (Transactions on Maritime Science, 2018)
This paper analyzes the shipowner’s role in the development process of ship’s computerized planned maintenance system database, paying specific attention to his/her impact on database quality grades resemblance equalization. The paper describes the database development process from the realization that the database is needed to the installation on board vessel, and all shipowner’s and developer’s actions in the process. The computerized databases of five shipping companies were tested using questionnaire developed for this purpose. The evaluation results are shown in several tables to facilitate overview and comparison of data. The paper provides the data of office user’s workload with regard to the administration and correction of data besides database quality grades: that data serves to portrait the relation between data quality in the databases and importance given to the process of development and maintenance of the databases. The analysis of the results yields numerical values as indicators of shipowner's input on the resemblance of grades of both scenarios and on the database quality grades resemblance equalization. The conclusion shows how the shipowner affects the ship's computerized planned maintenance system database and what actions should be performed to obtain the final product (database, i.e. data in the database) as good as possible and, thus, maintenance of the ship and the whole system. The expected results of the paper are: - To analyze in detail the database ordering and development process, - To pinpoint controlling areas for the database quality, - To analyze the shipowner’s impact on the database quality grades resemblance equalization.